(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate clinical presentation, diagnostic findings, and treatment outcomes of acute colonic diverticulitis at E Hospital. Methods: Retrospective descriptive study of 55 acute colonic diverticulitis patients (2021-2024). Statistical analysis using SPSS 20.0 software. Results: The patients had an average age of 47.15 ± 13.95 years; 74.55% male. Right-sided acute colonic diverticulitis 78.18%. Right lower quadrant pain 60%. CT detection 98.18%, ultrasound 61.28%. Conservative treatment success 90.91% (100% good outcomes). Surgery 9.09% with 60% good results. Complications only in left-sided cases (58.33% vs 0%), p < 0.001. Left-sided acute colonic diverticulitis showed higher fever (75% vs 11.6%), p < 0.001. Conclusion: Right-sided acute colonic diverticulitis more common with better outcomes. CT is gold standard. Conservative management highly effective, surgery reserved for complicated cases.